Women on boards and earnings management: What really matters? - Hala, Ganis Sepsika (UNIVERSITY OF MERDEKA MALANG, 2019)
The diversity of gender and income conservatism has been intriguing topics over the last decade. The effect of women who are more likely to be financially conservative than men will bring impact on the practices of conservative accounting, particularly when determining revenues for corporate governance. Therefore, we investigate the effects of women leaders in corporate business and their impacts on earnings management. The population of the study includes companies indexed in the Indonesia Stock Exchange, except for banking corporates. By using purposive sampling, 341 companies were selected for observation within six years. Total population sampling is 2046 data (firm-years). Hypothesis testing employed the multiple regression model on panel data with the Ordinary Least Square (OLS) approach. The estimation result of the Jones Model indicates women in top supervisory have no significant effect on earnings management while women in top management have a negative significant effect on earnings management. In addition, the hypothesis testing with the Kothari model demonstrates a negative significant effect of both women in top supervisory and women in top management toward earnings management. Therefore, we justify that women in top supervisory and women in top management bring prominent contributions to corporate business mainly in the financial sector, particularly in the improvement of financial reports by reducing the likelihood of earnings management practices.JEL Classification: D22, J16, G34DOI: https://doi.org/10.26905/jkdp.v23i4.3439